2021
DOI: 10.3389/fenvs.2021.766839
|View full text |Cite
|
Sign up to set email alerts
|

How Does Land Urbanization Promote CO2 Emissions Reduction? Evidence From Chinese Prefectural-Level Cities

Abstract: The process of land urbanization may result in a great change in land use structure, land use intensity, and efficiency, which could further lead to an increase in carbon dioxide (CO2) emissions. Despite rich literature on the link between urbanization and CO2 emissions, the mechanism through which land urbanization promotes CO2 emissions reductions has not been fully investigated. To address this gap, this study theoretically and empirically explores the mechanism of land urbanization’s influence on CO2 emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Accordingly, our findings support the suggestion that the Chinese authorities must strengthen the integrated utilization of energy and support information's spillover and technology advancement supported by land urbanization [ [50] , [51] , [52] ]. Besides this, our results support the suggestion that local government should strengthen land-use management, optimize the structure, reasonably control the intensity, and strive to incline the land-use efficiency [ 15 , 32 , 53 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Accordingly, our findings support the suggestion that the Chinese authorities must strengthen the integrated utilization of energy and support information's spillover and technology advancement supported by land urbanization [ [50] , [51] , [52] ]. Besides this, our results support the suggestion that local government should strengthen land-use management, optimize the structure, reasonably control the intensity, and strive to incline the land-use efficiency [ 15 , 32 , 53 ].…”
Section: Resultssupporting
confidence: 82%
“…First, the enhanced level of urban land construction significantly increases carbon's emissions and sharply declines absorption capacity of carbon [ 14 ]. The China's urban construction land enhanced to 55,155.5 square kilometers in 2017, from 20,877 square kilometers in 1999; thereby, displaying an upsurge of 164% [ 15 ]. In addition to this, the urban construction land's expansion is followed by a sharp increase in CO 2 emissions because this type of use represents CO 2 emissions' net source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al confirmed that there was a two-way causal relationship between the quality of land urbanization and carbon emissions, and the former had a negative impact on carbon emissions in various provinces [ 37 ]. Tang et al believed that low-level industrial development and land use management promote the increase of carbon emissions at the extensive land use stage, however, high-quality industrial development and land use optimization lower carbon emissions at the intensive land use stage [ 38 ]. A study has also demonstrated that intensive land use could reduce carbon emissions more effectively than extensive land use [ 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industrial land transformation effect refers to the expected effect obtained by the industrial industry in changing the original development model and progressive adjustment and reform. The expected effect of transformation contains several aspects such as industrial structure, development conditions, employment status, resource utilization, and ecological environment (Sun and Yuan, 2015;Tang and Hu, 2021;Tian et al, 2021) 1) to measure industrial land transformation effect by drawing on existing literature (Chen and Zhou, 2017;Liu H. et al, 2022;Li Q. et al, 2022;Pu and Zhang, 2022) and the actual development of industrial land in China.…”
Section: Indicator Selectionmentioning
confidence: 99%